Learner-Centered Curriculum: A Step Towards English Speaking Skill Improvement of Non-English Teachers - Dueñas Macías, Fredy Alonso (Universidad Pedagógica y Tecnológica de Colombia, 2013)
AbstractThis article aims at sharing the results of a small scale research project focused on guiding non-English speaking teachers of a Colombian bilingual school to perform their tasks in English within a school environment, through the implementation of a learner– centered curriculum based on English speaking-oriented workshops. Through theimplementation of this curriculum, it was seemed that the teaching, incorporation and use of some expressions of the English language, such as: greetings and farewells, common classroom expressions,commands and vocabulary, relate d to the specific subjects or topics those teachers teach, in addition to other aspects closely related to those topics, such as pronunciation. This project was conducted at a Colombian bilingual school with a group of 11 teachers in different subjects. Informal conversations with the teachers, interviews, questionnaires and workshops were used  to collect the information in this action research study. Findings revealed that through the use of speaking-oriented practice in the workshops, those teachers could reflect on their own foreign language learning process. They became confident and improved their speaking skills. They had the opportunity of working and enhancing their autonomous and cooperative learning skills.Key words: learner-centered curriculum, speaking-oriented workshops, autonomous learning, cooperative learning.